PENGARUH PEMBERIAN MINYAK BUAH MERAH (Pandanus conoideus oil) TERHADAP KADAR KOLESTEROL TOTAL TIKUS (Rattus norvegicus strain wistar) DENGAN DIET ATEROGENIK - Rohmawati, Ninna; Wuryaningsih, Emi Wuri (IKESMA, 2009)
Cardiovascular Disease (CVD) serves as the main cause of death in the world. The controllable main risk factor in Coronary Heart Disease (CHD) is LDL cholesterol content, triglyserida, and HDL cholesterol content in blood. The attempt to control coronary heart disease is by using antioxidant. Antioxidant can obstruct oxidation process and neutralize free radical to prevent various degenerative disease. This study was intended to find out the effect of red fruit oil (Pandanus conoideus oil) toward total cholesterol content of rat (Rattus novergicus strain wistar) with Aterogenic diet. This study was an experimental study. The design applied was complete randomized design with 3 repetitions and 8 treatment levels, namely P0 (diet standard), P1 (Aterogenic diet), P2 (S + MBM 0,12 ml/day), P3 (S + MBM 0,24 ml/day), P4 (S + MBM 0,36 ml/day), P5 (A + MBM 0,12 ml/day), P6 (A + MBM 0,24 ml/day), P7 (A + MBM 0,36 ml/day). The parameter was total cholesterol content. The process and data analysis applied Oneway Anova statistical test and followed with DMRT (Duncan Multiple Range Test). The result of Oneway Anova statistical test in confidence level 99% indicated that there was variance of significant total cholesterol content (p=0,000) among every treatment levels. The effect of using red fruit oil (Pandanus conoideus oil) toward total cholesterol content of rat (Rattus novergicus strain wistar) with aterogenic diet effective in 0,12 ml/day. The conclusion inferred from this study indicated that using red fruit oil (Pandanus conoideus oil) has significant effect toward reduction of total cholesterol content of rat (Rattus novergicus strain wistar) with aterogenic diet. Â  Key Words : Red fruit oil, total cholesterol content, aterogenic diet